Survival Analysis of Pneumonia Patients Using Kaplan-Meier and Cox Proportional Hazard Regression - Putri, Aulia Azira; Ananda, Dian Desti (Indonesian Council of Premier Statistical Science, 2025)
Pneumonia is one of the leading infectious diseases in the world, especially in the elderly and patients with complications. This study aims to analyze the survival of pneumonia patients treated in the ICU room of Hospital X by 2024 using the Kaplan-Meier method and Cox Proportional Hazard regression. The data used consisted of 37 patients, with independent variables in the form of age and type of pneumonia (mildness, sepsis, and other complications), and dependent variables in the form of patient survival time. The Kaplan-Meier analysis showed that patients with >60 years of age and complicated types of pneumonia tended to have lower survival rates. However, the results of the Log-Rank test showed that there was no statistically significant difference between age groups and types of pneumonia on survival (p > 0.05). The results of the Cox regression also showed that no variables had a significant effect on the patient's risk of death, although types of pneumonia with other complications showed a significant tendency at the level of 10% (p = 0.0699). This study demonstrates the importance of considering disease severity in the evaluation of the risk of death of pneumonia patients, as well as the need for further research with larger sample counts and additional clinical variables.